SYEKH SULAIMAN AL-RASULI TOKOH PENDIDIKAN ISLAM BERCORAK KULTURAL - Kosim, Muhammad (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Shaykh Sulayman al-Rasuli (1871-1970 AD) was consistent scholar of Minangkabau to maintain i'tiqadAhl al-Sunnah wa al-Jama'ah and the Shafi'i school. He was known as a master scholar of fiqh and becamehead of the first Syar'iyah Court in Central Sumatra (based in Bukittinggi). He was also mentioned aspioneer of Islamic Education. His pioneer can be seen from two things. First, as practitioner of education.He taught and led the MTI Canduang. While teaching, he accepted and practiced the educational reform inthe form of: 1) the model learned from one book into many books to understand specific areas of knowledge;2) change of Halaqah system at the mosque became a system of class in madrassas. Secondly, as a thinker ofIslamic Education. His thought can be found in some of his writings, related to human nature, the purpose ofeducation, materials, educators, learners, methods, and informal education. When constructed madrassah andwrote down his thoughts, he always approached Minangkabau’s culture. Therefore he was worth mentionedthe cultural figure of Islamic education.